2010
DOI: 10.1038/onc.2010.256
|View full text |Cite
|
Sign up to set email alerts
|

From smoking to lung cancer: the CHRNA5/A3/B4 connection

Abstract: Nicotinic acetylcholine receptors (nAChRs) are ligand-gated ion channels that modulate key physiological processes ranging from neurotransmission to cancer signaling. These receptors are activated by the neurotransmitter, acetylcholine, and the tobacco alkaloid, nicotine. Recently, the gene cluster encoding the α3, α5 and β4 nAChR subunits received heightened interest after a succession of linkage analyses and association studies identified multiple single nucleotide polymorphisms (SNPs) in these genes that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 164 publications
(209 reference statements)
1
36
0
Order By: Relevance
“…The receptors bind to nicotine, N’-nitrosonornicotine and other potential carcinogens, leading to genetic mutations and neoplastic transformation[34]. SNPs in CHRNA5-CHRNA3-CHRNB4 could be able to influence the binding function, thus influence individual lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…The receptors bind to nicotine, N’-nitrosonornicotine and other potential carcinogens, leading to genetic mutations and neoplastic transformation[34]. SNPs in CHRNA5-CHRNA3-CHRNB4 could be able to influence the binding function, thus influence individual lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…8,28 nAchRs have been noted to promote a nicotine-stimulated epithelial-to-mesenchymal transition (EMT) in a variety of human cancer cell lines, especially in small cell lung cancer and non-small cell lung cancer. 12,13 Several studies have reported roles of nAchRs in carcinogenesis, proliferation, angiogenesis, inhibition of apoptosis and metastasis in breast, lung and colon cancers. 14e17, 29,30 In studies of colon cancer and gastric cancer, a7-nAChR was found to play a dominant role in mediating cancer progression and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…These pathways need also to be considered when developing nAChR drugs for chronic treatment. The heteromeric α3α5β4 nAChR could be another important target, since genetic studies show a possible role of the CHRNA5/A3/B4 gene cluster in the development of lung cancer which could lead to altered gene expression, but also to changed receptor function [38]. …”
Section: Introductionmentioning
confidence: 99%